2015
DOI: 10.17159/2224-7912/2015/v55n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Die effek van 'n troeteldier-ondersteunde leesprogram op woordherkenningsvaardighede van graad 3-kinders

Abstract: Die doel van die huidige studie was om die effek van 'n troeteldier-ondersteunde leesprogram (TOL) op die woordherkenningsvaardighede van graad 3-kinders te bepaal. Al die kinders wat met behulp van die ESSI Leestoets as nievaardige lesers (N=102) geïdentifiseer is, is ewekansig toegewys aan drie eksperimentele groepe en een kontrolegroep. Een maal per week vir 10 weke lank het die Leeshondgroep (n=27) vir 'n leeshond in die teenwoordigheid van 'n Pets as Therapy-vrywilliger gelees, die Volwassenegroep (n=24) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…This review found only two group design studies based specifically on the R.E.A.D programme. The two studies that were included in this review found some evidence of impact on pupils’ reading skills (Le Roux et al, 2014, 2015). However, these studies were rated low quality (1) as a result of small samples and poor design.…”
Section: Resultsmentioning
confidence: 99%
“…This review found only two group design studies based specifically on the R.E.A.D programme. The two studies that were included in this review found some evidence of impact on pupils’ reading skills (Le Roux et al, 2014, 2015). However, these studies were rated low quality (1) as a result of small samples and poor design.…”
Section: Resultsmentioning
confidence: 99%
“…E doze autores,Beetz (2013), Takács e Szalai (2015),Santos (2016),Nobre (2017),Pereira (2017),Dicé (2017),Nakajima (2017),, Jorge(2018), Parizotto e Pereira(2018),Oliveira (2019) eFung (2019), relataram tanto ganhos psicológicos quanto cognitivos.A partir da análise dos resultados das pesquisas percebemos que os trabalhos, que relataram como achados o desenvolvimento cognitivo das crianças, apresentaram como tendência a utilização da leitura como objeto de interação.Importante frizar que o referencial teórico que fundamenta seis dos 17 trabalhos analisados,Gee et al (2017),Beetz (2013),Nakajima (2017),Dicé et al (2017), Tissen et al. (2007 e LeRoux et al (2015), que utilizaram como parte do seu referencial o estudo de KurtKotrschal & Brita Ortbauer (2003), tinham como foco de pesquisa verificar os efeitos causados pela presença de um cão em sala de aula. A hipótese dos pesquisadores era de que o cão atuaria como lubrificante social, tornando as crianças mais introvertidas, mais abertas à comunicação e amorteceria o comportamento daquelas mais extrovertidas melhorando a integração social do grupo.…”
unclassified